Penerapan Algoritma C4.5 untuk Prediksi Kepuasan Pelayanan Pasien Puskesmas Brangsong I - Moh Umar Nauful Fajri; Siti Noor Chotimah (Jurnal Cakrawala Informasi, 2024)
The quality of health services is essential to public health center services. One of the influencing factors is the level of patient satisfaction with the services provided. This research aims to predict patient satisfaction at Brangsong I Community Health Center using the C4.5 algorithm and determine the accuracy of the results. The first step is the collection of data which is carried out by the distribution of questionnaires to be completed by patients, then secondly the results of the questionnaire are analyzed for a summary in Excel form. Perform calculations to find the gain and entropy. The results obtained by the service flow obtained the highest gain, which was 0.4974. Then, calculations are performed on the dimensions of the service flow until its completion. The research testing process used RapidMiner software to create a decision tree. The accuracy of the calculation results is 98%. The value of the gain can be influenced by the treatment reserved for the data used during the search. Based on the analysis results, it is hoped that it can improve the performance of Brangsong I Community Health Center by providing better services to patients.